2018
DOI: 10.1371/journal.pone.0191258
|View full text |Cite
|
Sign up to set email alerts
|

A non-linear pharmacokinetic-pharmacodynamic relationship of metformin in healthy volunteers: An open-label, parallel group, randomized clinical study

Abstract: BackgroundThe aim of this study was to explore the pharmacokinetic-pharmacodynamic (PK-PD) relationship of metformin on glucose levels after the administration of 250 mg and 1000 mg of metformin in healthy volunteers.MethodsA total of 20 healthy male volunteers were randomized to receive two doses of either a low dose (375 mg followed by 250 mg) or a high dose (1000 mg followed by 1000 mg) of metformin at 12-h intervals. The pharmacodynamics of metformin was assessed using oral glucose tolerance tests before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 26 publications
4
26
1
Order By: Relevance
“…30 This is especially so at higher metformin doses, consistent with a local antihyperglycaemic effect of unabsorbed metformin within the intestine. 30 In addition, metformin is known to accumulate in intestinal tissues after dosing, as described above. These observations are consistent with a clinically significant antihyperglycaemic action of metformin in the gut.…”
Section: Intestinal Disposal Of Glucosementioning
confidence: 66%
See 1 more Smart Citation
“…30 This is especially so at higher metformin doses, consistent with a local antihyperglycaemic effect of unabsorbed metformin within the intestine. 30 In addition, metformin is known to accumulate in intestinal tissues after dosing, as described above. These observations are consistent with a clinically significant antihyperglycaemic action of metformin in the gut.…”
Section: Intestinal Disposal Of Glucosementioning
confidence: 66%
“…Clinical studies have confirmed that the antihyperglycaemic action of immediate‐release or prolonged‐release metformin on blood glucose is dose‐dependent but not related clearly to systemic exposure to metformin, as measured by plasma concentration‐time curves . This is especially so at higher metformin doses, consistent with a local antihyperglycaemic effect of unabsorbed metformin within the intestine . In addition, metformin is known to accumulate in intestinal tissues after dosing, as described above.…”
Section: Antihyperglycaemic Mechanismsmentioning
confidence: 99%
“…Pharmacokinetic parameters can be modified after two different secondary doses of metformin (250 or 1000 mg). In this case, C max varied from 591.1 ± 247.5 to 1937.5 ± 863.0 µg/ml), whereas T max and t 1/2 did not show dose-dependent changes ( Chung et al., 2018 ). A recent study showed that high-intensity interval exercise diminishes metformin concentration (2–3 h), increases C max (4.4 ± 2.5 µg/ml) and diminishes T max (2.7 ± 0.9 h) ( Nikolaidis et al., 2020 ).…”
Section: Pharmacokinetics Of Metforminmentioning
confidence: 76%
“…Scheen [60] and Graham et al [27] indicated that metformin shows nonlinear pharmacokinetics caused by a reduced bioavailability at higher doses. Moreover, Chung et al [11] revealed that effects on glycaemia did not linearly increase with higher doses of metformin in humans. The results of these studies led to the assumption that a similar phenomenon could have been possible in our study.…”
Section: Discussionmentioning
confidence: 99%